PEER EDUCATOR NUTRITION EDUCATION IN PREVENTION OF ANEMIA INCIDENCE - Kusumawati, Erna; Rahardjo, Setyowati; Kurnia Putri, Widya Ayu (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2019)
Teenagers are a growth period that requires higher nutrients such as iron. Factors that can affect the incidence of anemia are the knowledge and attitudes of teenagers. The result of previous studies showed that the average level of knowledge, attitude, and prevention of nutritional anemia in teenager girls in the working area of the Kedungbanteng health center 1 was still low. Nutrition education that was started often used is peer education. This study purpose to analyze the influence of nutrition education on increasing knowledge and attitude of peer educator in the effort of peer education development about prevention of anemia incidence. The method research is quasi-experimental with pretest and posttest design. The sampling technique using a total sampling of 49 teenagers in the working area of Kedungbanteng health center. The result of the statistical test using a wilcoxon test. The result showed that there is a difference of knowledge and attitude of peer educator after given nutrition education ( p = 0,000 ; p = 0,000). There is a difference of knowledge and attitude of peer educator after given nutrition education.